HUBUNGAN AKSES INFORMASI, PERAN PETUGAS KESEHATAN DAN DUKUNGAN KELUARGA DENGAN CAKUPAN PEMERIKSAAN INSPEKSI VISUAL ASAM ASETAT (IVA) PADA WANITA USIA SUBUR (WUS) DI WILAYAH KERJA PUSKESMAS KUTARAYA KABUPATEN OKI TAHUN 2020: Armieka Triyuni, Sendy Pratiwi Rahmadhani, Sri Handayani - Armieka Triyuni (JURNAL SMART ANKes, 2020)
The Incident of Cervical Cancer in Indonesia shows 17 per 100,000. The lower coverage of early protection becomes one reason why cervical cancer continues to get higher. For more than 50 percent of women in Indonesia who are diagnosed with cancer have never been early detected before. The objective of this research is aimed to know the correlation of information access, the role of health officers and family supports with the coverage of visual inspection examination of acetic acid (IVA) to the women of fertile age (WUS) in the working area of Puskesmas Kutaraya OKI Regency in 2020. It is a quantitative research with Cross Sectional design. The population in this research is all women of fertile age (WUS) in the working area of Puskesmas Kutaraya OKI Regency amounts of 1753 people. The number of sample was 137 WUS that was taken by using accidental sampling technique. The data was analyzed by Chi Square test. The result of statistical test shows that there is a correlation of information access with coverage of IVA examination ( P=0.018), there is a correlation between the role of health officers with coverage of IVA examination (P=0.000), there is a correlation between the family supports with the coverage examination IV A (P=0.006). The conclusion of this research is there is a correlation of information access, the role of health officers and family supports with the coverage of visual inspection examination of acetic acid (IVA) to the women of fertile age (WUS) in the working area of Puskesmas Kutaraya OKI Regency in 2020.